A case of reactive arthritis after enteritis in in a 12-year-old boy - Peter Chun; Young Jin Kim; Young Mi Han; Young Mi Kim (Korean Pediatric Society, 2011)
Reactive arthritis comprises a subgroup within infection-associated arthritides in genetically susceptible hosts. Researchers and clinicians recognize two clinical forms of reactive arthritis which occurs after genitourinary tract infection and after gastrointestinal tract infection. Chlamydia infection has been implicated as the most common agent associated with post-venereal reactive arthritis. Studies have proposed Shigella infection, Salmonella infection, or Yersinia infection as the microorganisms responsible for the post-dysenteric form. The human leukocyte antigen (HLA)-B27 antigen is the best-known predisposing factor. We report a case of HLA-B27-associated reactive arthritis after Salmonella enteritis at Pusan National University hospital.